2015 6th International Conference on Automation, Robotics and Applications (ICARA) 2015
DOI: 10.1109/icara.2015.7081127
|View full text |Cite
|
Sign up to set email alerts
|

Human-driven multi-robot design process for social interactions with children on complex environments

Abstract: Robots have been traditionally in operation away from people, for instance in industrial environments. More recently, there has been a trend for bringing robots to market for helping people. In particular, children constitute a challenging group for robot interaction, due to their curiosity and energy, as well as safety concerns. This paper describes the construction process of an external structure for a fleet of mobile robots designed for interactions with children in a hospital environment. We address sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Under the scope of the AHA project, we have been applying this process to the design of mobile robots targeting new user groups. This "nurse" mobile robot, although posing similar challenges as the ones described by Gonçalves and Arsenio [15], also adds new requirements. Elderly people, athletes and patients poses specific requirements that often differ from those for children in hospitals.…”
Section: Robot Design For Human Augmented Assistancementioning
confidence: 85%
See 3 more Smart Citations
“…Under the scope of the AHA project, we have been applying this process to the design of mobile robots targeting new user groups. This "nurse" mobile robot, although posing similar challenges as the ones described by Gonçalves and Arsenio [15], also adds new requirements. Elderly people, athletes and patients poses specific requirements that often differ from those for children in hospitals.…”
Section: Robot Design For Human Augmented Assistancementioning
confidence: 85%
“…Contrary to the Monarch robots, there is no multifunctional face on the nurse robots. [15]. In contrast to the professional look and feel for the nurse robot, the monarch robots are character-like, but not resembling any particular known artificial character.…”
Section: Ergonomics and Human Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a way, all of them fall within our scope; the difference among them comes from the fact that some of them combine software and hardware (4-10), while others are usually only software (1)(2)(3). [43,60] offer exhaustive and historical reviews of robots. Specifically, in a healthcare context, we found that the most accurate definition is related to the central care concept.…”
Section: Discussionmentioning
confidence: 99%